Moving Beyond Initiative: The Reconceptualization and Measurement of Unethical Pro-organizational Behavior - Wang, Jing; Shi, Wei; Liu, Guoqin; Zhou, Li (Frontiers in Psychology, 2021)
Despite the fact that unethical pro-organizational behavior (UPB) has become a theoretical topic in the academic field and that fruitful achievements have been explored in the past decade, organizational researches have largely assumed that UPB is an initiative and voluntary behavior from the perspective of organizational identity and social exchange. In this paper, the authors argue that previous researches have traditionally considered only a very narrow subset of UPB, focusing almost exclusively on extreme voluntary cases which are not reflective of typical UPB. Instead of being primarily voluntary, typical UPB can be either proactive or compulsory in nature. It is therefore recommended that UPB be studied from the perspective of the degree to which the motivations emanate from the self. To facilitate this, the authors reconceptualize the UPB construct and then develop a series of UPB scales. Using 6 samples, the authors demonstrate the construct validity, reliability, and acceptable psychometric properties of the UPB scales. Future directions in UPB research are discussed.